Medical, psychological and socio-economic implications of chronic hand eczema: a cross-sectional study - Cazzaniga, Simone; Ballmer‐Weber, B. K.; Gräni, N.; Spring, P.; Bircher, A.; Anliker, M.; Sonntag, A. K.; Piletta, P.; Huber, C.; Borradori, L.; Diepgen, Thomas L.; Apfelbacher, C.; et al. (Journal of the European Academy of Dermatology and Venereology, 2016)
Background Hand eczema (HE) is a common skin disease with major medical psychological and socio-economic implications. Onset and prognosis of HE are determined by individual as well as environmental factors. So far, most epidemiological data on HE have been reported from Scandinavian and recently German studies. Objective To investigate the characteristics and medical care of patients with chronic HE (CHE) in Switzerland, and identify risk factors. Methods In this cross-sectional study, data from patients with chronic HE were obtained by means of medical history, dermatological examination and patient questionnaires. Multiple logistic regression analysis was applied to identify risk factors for high severity and dermatology life quality index (DLQI). Results In seven dermatology departments, 199 patients (mean age 40.4 years, 50.8% female) with CHE (mean duration 6.6 years) were enrolled. Moderate to severe HE was reported by 70.9% of patients, and was associated with age <30 or >50 years, localization of lesions and pruritus. Because of the CHE, 37.3% of patients were on sick leave over the past 12 months, 14.8% had changed or lost their job. Practically all patients applied topical therapy, 21% were treated with alitretinoin, and 21% with psoralen plus UVA light (PUVA). The effects on the health-related quality of life was moderate to large in 33.7% and 39.4% of CHE patients, respectively. Factors associated with a high impact on DLQI (mean 9.7 ± 5.8) were female sex, lesions on back of the hands and pruritus as well as mechanical skin irritation and wearing gloves. Conclusion In agreement with recent studies, the Swiss data demonstrate the high impact of CHE on medical well-being, patient quality of life and work ability. As it is associated with an intense use of health care services, high rate of sick leave, job loss and change, CHE may cause a high socio-economic burden.